Community violence exposure, family management practices, and substance use in youth: a cross-cultural study. (June 2017) - Kliewer, Wendy; Pillay, Basil J; Borre, Alicia; Zaharakis, Nikola; Drazdowski, Tess; Jäggi, Lena
Associations between community violence exposure, family management practices, and substance use were compared in a sample of early adolescents in low-income communities from the United States ( N  = 151; M age = 12.71 years, standard deviation = 0.65; 50.3% female) and South Africa ( N  = 175; M age = 12.55 years, standard deviation = 0.85; 64.6% female) using home interviews with youth and their maternal caregivers. Past year victimization was associated with recent youth substance use. The moderating role of family management practices varied by type of practice (e.g., parental knowledge, control, solicitation, or child disclosure), reporter, and country. High parental knowledge reported by caregiver was protective against substance use only for South African youth. In youth reports, parental knowledge was protective across the United States and South Africa. Youth reports of their disclosure to parents were negatively associated with substance use in the United States but not South Africa. These data highlight the importance of considering both ecological context and reporter in the links between violence exposure, parenting, and substance use in youth.